Long-term variation of coronal holes latitudinal distribution - Maghradze, D. A.; Chargeishvili, B. B.; Japaridze, D. R.; Oghrapishvili, N. B.; Chargeishvili, K. B.
We study the evolution of the latitudinal distribution of coronal holes using the Solar and Heliospheric Observatory (SOHO)/Extreme ultraviolet Imaging Telescope (EIT) 195 ˚Adata from 1996 May to 2020 April. To measure the presence of coronal holes at a given latitude, we use the presence factor, which estimates the length of an object along a given parallel, expressed as a percentage of half of the equator length. By semi-automatic processing of the data series, we obtained the 361 ×7346 latitude–time matrix. The corresponding diagram shows the significant difference in evolutionary shapes of a latitudinal distribution of non-polar and polar coronal holes. However, the morphology of the evolutionary picture and the migration route of the geometric centre of activity of the coronal hole in the diagram indicate that non-polar and polar coronal holes have the same driving mechanism. It is believed that the migration of the centre of activity of the coronal hole in the latitude–time diagram is a combination of two opposite migration paths. They intersect at the equator and diverge to opposite poles, where they form the so-called polar coronal holes, then again mo v e to lower latitudes, and this happens cyclically. Determining the opposite migration paths by antiphase sinusoids, their deviation from antiphase determines the detected north–south asymmetry in the activity of the coronal hole.
Keywords: Astronomy